The razor's edge: Australian rock music impairs men's performance when pretending to be a surgeon. Issue 11 (12th December 2016) - Fancourt, Daisy; Burton, Thomas MW; Williamon, Aaron
Abstract: Objective: Over the past few decades there has been interest in the role of music in the operating theatre. However, despite many reported benefits, a number of potentially harmful effects of music have been identified. This study aimed to explore the effects of rock and classical music on surgical speed, accuracy and perceived distraction when performing multiorgan resection in the board game Operation . Design: Single‐blind, three‐arm, randomised controlled trial. Setting: Imperial Festival, London, May 2016. Participants: Members of the public ( n = 352) aged ≥ 16 years with no previous formal surgical training or hearing impairments. Methods: Participants were randomised to listen through noise‐cancelling headphones to either the sound of an operating theatre, rock music or classical music. Participants were then invited to remove three organs from the board game patient, Cavity Sam, using surgical tweezers. Main outcome measures: Time taken (seconds) to remove three organs from Cavity Sam; the number of mistakes made in performing the surgery; and perceived distraction, rated on a five‐point Likert‐type scale from 1 (not at all distracting) to 5 (very distracting). Results: Rock music impairs the performance of men but not women when undertaking complex surgical procedures in the board game Operation, increasing the time taken to operate and showing a trend towards more surgical mistakes. In addition, classical music was associated with lower perceived distraction during the game, but this effect was attenuated when factoring in how much people liked the music, with suggestions that only people who particularly liked the music of Mozart found it beneficial. Conclusions: Rock music (specifically Australian rock music) appears to have detrimental effects on surgical performance. Men are advised not to listen to rock music when either operating or playing board games.